A cultura local e as experiências de músico sonoplasta no grupo Xamã: os contadores de histórias - FERRO, Kélem Carla Alves (Universidade Federal do Pará, 2020)
The work as a music educator in public schools of the state education network has among its many challenges the reduction of distances between the academic curriculum formation of the music teacher and the musical culture brought by the students. The musical experience in the group Xamã brings, in the scope of artistic production, the practice of accompaniment and arrangement thought to express in the music, local, thematic and ethnic literatures. The academic training of the music teacher has the characteristic of emphasizing the European musical tradition and of making it an example in the construction of formal knowledge. This action as a cultural action has direct reverberation in the practices of music teachers in public schools throughout Brazil, establishing contradictions between the academic formation, the reality presented in schools, the curricular parameters of the discipline and the recent demands pointed by ethnomusicology for musical education . In this sense, the artistic practice that involves literature and music with an emphasis on the diversity of social groups also presents itself as a possibility of building musical knowledge, inside and outside the classroom, based on experiences of appreciation, contextualization and shared musical creation With the students.